Effect of the Static Strength of a Metal on Long-Rod Penetration at Low Velocities - Stepanov, G.V.; Kharchenko, V.V. (Проблемы прочности, 2000)
The effect of the static strength (yield stress) of a material on major penetration parameters (specific work of deformation and penetration force determined by the pressure at the rod-cavity contact surface) was examined. The analytical equations and quantitative estimates of specific work spent for formation of spherical and cylindrical cavities and of the pressure at the surface of such cavities at their static expansion were obtained for the rigidplastic and elastoplastic models of the material. The estimates of specific work of deformation at the formation of the spherical cavity in the plate and of the penetration of a rigid rod are shown to be adequate. The influence of strain hardening on a maximum radial stress on the cavity surface was evaluated. The resistance to penetration and the expansion of a cavity are shown to be strongly influenced by the elastic compressibility of a material in the inelastic region at low penetration velocities. The kinetics of the stress-strain state of the material at the formation of the cavity was analyzed for the case of considerable deformation of a rod at penetration.